Emergency Room Doctor Needs Analysis of RSI Ibnu Sina Padang During Covid-19 Pandemic - Nurul Fitri Khumaira; Hardisman; Erlinengsih (Riviera Publishing, 2022)
Introduction: One of the successes in ensuring the quality of health services is the quality of Health Human Resources. The quality of human resources is influenced by their availability. Therefore, hospital management must be concerned with planning the ideal needs of human resources. Workload Indicator Staffing Need (WISN) is a method to calculate human resources requirements based on real workload. This study aims to determine the ideal number of doctors based on workload analysis in the emergency unit of RSI Ibnu Sina Padang during the Covid-19 pandemic using the WISN (Workload Indicator Staffing Needs) method. Methods: qualitative descriptive research. This research was conducted in Emergency Unit RSI Ibnu Sina Padang from December 2021 to March 2022. Result: working time of Emergency unit doctors was 117,180 minutes/year. Workload standards are 16 main tasks and a result of the allowance standard is 0.397. The WISN result of calculating doctor's needs in emergency units of RSI Ibnu Sina Padang during the Covid-19 pandemic is 6,953 or rounded up to 7 doctors. It means that it still needs 1 person based on workload analysis. Conclusion: There are several additional items of activities of emergency room doctors during the Covid-19 pandemic which will impact the increasing workload of ER (Emergency Room) doctors and the length of service time in the emergency room unit. Hospital management should plan the need of health workers based on real workloads to improve service quality by maintaining health workers and their patient safety.